[(25•7-13^2)•12-8^2]•2^17-4^10
Răspunsuri la întrebare
Răspuns de
0
[(25•7-13^2)•12-8^2]•2^17-4^10 =
= [(175 - 169)×12 - 64]×2^17 - 2^2×10 =
= (6 ×12 - 64)×2^17 - 2^20 =
= (72 - 64) × 2^17 - 2^20 =
= 8 × 2^17 - 2^20 =
= 2^3 × 2^17 - 2^20 =
= 2^3+17 - 2^20 =
= 2^20 - 2^20 =
= 0
= [(175 - 169)×12 - 64]×2^17 - 2^2×10 =
= (6 ×12 - 64)×2^17 - 2^20 =
= (72 - 64) × 2^17 - 2^20 =
= 8 × 2^17 - 2^20 =
= 2^3 × 2^17 - 2^20 =
= 2^3+17 - 2^20 =
= 2^20 - 2^20 =
= 0
Alte întrebări interesante
Matematică,
8 ani în urmă
Chimie,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă